Everyday Stress Response Targets in the Science of Behavior Change - Smyth, Joshua M. (Behav Res Ther, 2017)
Stress is an established risk factor for negative health outcomes, and responses to everyday stress can interfere with health behaviors such as exercise and sleep. In accordance with the Science of Behavior Change program, we apply an experimental medicine approach to identifying stress response targets, developing stress response assays, intervening upon these targets, and testing intervention effectiveness. We evaluate an ecologically valid, within-person approach to measuring the deleterious effects of everyday stress on physical activity and sleep patterns, examining multiple stress response components (i.e., stress reactivity, stress recovery, and stress pile-up) as indexed by two key response indicators (negative affect and perseverative cognition). Our everyday stress response assay thus measures multiple malleable stress response targets that putatively shape daily health behaviors (physical activity and sleep). We hypothesize that larger reactivity, incomplete recovery, and more frequent stress responses will negatively impact health behavior enactment in daily life. We will identify stress-related reactivity, recovery, and response in the indicators using coordinated analyses across multiple naturalistic studies. These results are the basis for developing a new stress assay and replicating the initial findings in a new sample. This approach will advance our understanding of how specific aspects of everyday stress responses influence health behaviors, and can be used to develop and test an innovative ambulatory intervention for stress reduction in daily life to enhance health behaviors.